Disinhibition of Human Primary Somatosensory Cortex After Median Nerve Transection and Reinnervation - Nordmark, Per F.; Johansson, Roland S. (Frontiers in Human Neuroscience, 2020)
Despite state-of-the-art surgical and postoperative treatment, median nerve transection causes lasting impaired hand function due to limitations in the nerve’s reinnervation ability. The defective innervation and thus controllability of the affected hand can shape the brain's control of manual behaviors. Earlier studies of changes in processing of tactile stimuli have focused mainly on stimulation of the reinnervated hand and lack sufficient control over the brain's use of the tactile input in perceptual terms. Here we used fMRI to measure brain activity (BOLD-signal) in eleven people with median nerve injury and in healthy controls (N=11) when performing demanding tactile tasks using the tip of either the index or little finger of either hand. For the nerve-injured group, the left median nerve had been traumatically transected in the distal forearm and surgically repaired on average 8 years before the study. The hand representation of their contralesional (right) primary somatosensory cortex (S1) showed greater activity compared to controls when the left reinnervated index finger was used, but also when the left-hand little finger and the fingers of the right hand innervated by uninjured nerves were used. We argue that the overall increase in activity reflects a general disinhibition of contralesional S1 consistent with an augmented functional reorganizational plasticity being an ongoing feature of chronic recovery from nerve injury. In addition, the nerve-injured showed increased activity within three prefrontal cortical areas implicated in higher-level behavioral processing (dorsal anterior cingulate cortex, left ventrolateral prefrontal and right dorsolateral prefrontal cortex), suggesting that processes supporting decision-making and response-selection were computationally more demanding due to the compromised tactile sensibility.